Fashion Orientation among Muslim Female Students (Santriwati) - Farida Farida; M. Nazaruddin (International Journal of Business, Economics, and Social Development, 2020)
This study examines the orientation of fashion products consumed by students of the Al-Hanafiah Foundation Putri Muslimat Islamic Boarding School. This study examines the orientation of fashion products consumed by Muslim female students (santriwati). Researchers use qualitative research methods in collecting and analyzing data. Researchers also use the perspective of postmodern studies in the view of Jean P. Audillard and other postmodern figures as research instruments in conducting research approaches. Data analysis techniques used in this study refer to the interactive analysis method using data reduction, data presentation, concluding, and data verification. The results showed that the fashion consumed by Muslim female students at the Al-Hanafiah Foundation Putri Muslimat Islamic Boarding School is oriented to beauty, confidence, prestige, self-image, identity, and oriented as group cohesiveness.